Beyond the gaze: seeing and being seen in contemporary queer media - Morse, Nicole; Herold, Lauren (Jump Cut, 2021)
Exploring haptic visuality in contemporay queer film and TV, this essay engages what feminist media producer Joey Soloway calls "feeling seeing" as a methodological approach to analyzing the affective dimensions of queer love and vulnerability on screen from Carol to "San Junipero" to Moonlight.